International prestige of sports biomechanics serials - Knudson, D.; Ostarello, J. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
This study measured the prestige of seventy-five serials in the international sports biomechanics community. The 2007 ISBS membership was surveyed by electronic mail and asked to rate the typical quality/prestige of the serials on a five point scale. Descriptive statistics of ratings were calculated for the sixty-five respondents and correlated with the 2006 impact factor (IF) reported in the Journal Citation Reports. Mean ratings showed that international perception of sports biomechanics serials was unique from other areas of biomechanics and this perception was weakly (r = 0.34) correlated with the IF. Based on these data, it appears that the IF is an inappropriate index for evaluating the international prestige of sports biomechanics serials.